"THE IMPACT OF TAX INCENTIVES, TAX SANCTIONS, AND SOCIALIZATION ON TAX COMPLIANCE AMONG MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) IN WEST JAKARTA DURING THE COVID-19 PANDEMIC" - Steelyana W, Evi; Maarif, Syamsul (SEEIJ (Social Economics and Ecology International Journal), 2023)
The purpose of this study is to empirically examine the effect of tax regulation during on covid19 pandemic. There are factors which have been implemented which are tax incentives, government incentives on regulation number 23 of 2018, and tax sanctions on the level of taxpayer compliance of small and medium enterprises (SME). This study uses primary data in the form of a questionnaire. The analytical method used in this study is SEM-PLS analysis with Level of Taxpayer Compliance of Small and Medium Enterprises (SME) as the dependent variable and tax incentives, socialization of government regulation number 23 of 2018, and tax sanctions as an independent variable. The results of this study showed that tax incentives , and socialization of government regulation number 23 of 2018, have no effect on the level of taxpayer compliance of small and medium(SME), while the tax sanctions variable has a positive and significant effect on the level of taxpayer compliance of small and medium (SME).